2019
DOI: 10.1002/ehf2.12474
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cardiac function in acute heart failure patients with mid‐range ejection fraction: AURORA study

Abstract: Aim The factors correlated with prognosis in heart failure with mid‐range ejection fraction (HFmrEF) is unclear, especially for acute heart failure (AHF) with HFmrEF. Thus, we investigated the factors correlated with the improvement in the ejection fraction (EF) over 1 year in AHF patients with HFmrEF. Methods and results In Acute Heart Failure Registry in the Osaka Rosai Hospital, we examined 159 consecutive HFmrEF patients out of 1051 HF patients who were admitted to our hospital for AHF from January 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…NYHA grade, right ventricular function, left ventricular function, and LVEF were important methods to assess patient's cardiac functional status. 9,10 With the deterioration of cardiac function, the perioperative circulation support became increasingly important. 11,12 Herein, we found that the application of V-A-ECMO was associated with NYHA grade for recipients, indicating that when a decision needed to be made regarding whether or not to continue V-A-ECMO support at the end of surgery, it was easier for the clinicians to maintain the ECMO for patient with the NYHA grade of III/IV.…”
Section: Discussionmentioning
confidence: 99%
“…NYHA grade, right ventricular function, left ventricular function, and LVEF were important methods to assess patient's cardiac functional status. 9,10 With the deterioration of cardiac function, the perioperative circulation support became increasingly important. 11,12 Herein, we found that the application of V-A-ECMO was associated with NYHA grade for recipients, indicating that when a decision needed to be made regarding whether or not to continue V-A-ECMO support at the end of surgery, it was easier for the clinicians to maintain the ECMO for patient with the NYHA grade of III/IV.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available evidence is focused on Europe and America, with only a few studies from Israel and Japan in Asia and little from China [18][19][20]. The relationship between serum albumin and short-term mortality is not completely clear.…”
Section: Introductionmentioning
confidence: 99%